2020
DOI: 10.1038/s41598-020-71627-1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a novel functional test for assessing metamorphopsia using epiretinal membranes as a model

Abstract: Current tests for assessing metamorphopsia do not account for confounders such as perceptual filling-in and spatial redundancy, which affect its sensitivity and repeatability. This proof-of-concept study aimed to assess the performance of a novel laboratory-based psychophysical test (Line Sag Test, LST) which addresses these issues for quantification of metamorphopsia in idiopathic epiretinal membranes. The LST quantifies perpendicular metamorphopsia at three eccentricities (3°, 6°, and 9°) along eight meridia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…35,36 Data from all of the healthy participants and 25 of the glaucoma participants have been reported in part in previous investigations . [31][32][33][36][37][38][39] As per previous studies, [31][32][33]37 exclusion criteria for all cohorts included spherical equivalent refractive error outside the range of ±6.00 dioptres (D), astigmatism greater than 3.00 D and the presence of macula pathology in the included eye. Written consent to utilise clinical data for research purposes was obtained as per protocols approved by the University of New South Wales, Australia, Human Research Ethics Advisory Panel.…”
Section: Study Cohortsmentioning
confidence: 99%
“…35,36 Data from all of the healthy participants and 25 of the glaucoma participants have been reported in part in previous investigations . [31][32][33][36][37][38][39] As per previous studies, [31][32][33]37 exclusion criteria for all cohorts included spherical equivalent refractive error outside the range of ±6.00 dioptres (D), astigmatism greater than 3.00 D and the presence of macula pathology in the included eye. Written consent to utilise clinical data for research purposes was obtained as per protocols approved by the University of New South Wales, Australia, Human Research Ethics Advisory Panel.…”
Section: Study Cohortsmentioning
confidence: 99%
“…One such method called the line sag test (LST) is a computerized psychophysical test in which the observer is presented briefly with a curved line and asked to report whether the line appears to bulge inwards or outwards. 44 Using a staircase procedure, an algorithm neutralizes the amount of perceived sag by presenting a curve at the opposite direction to the response of the patient in the next trial. Comparing the results to those obtained with a traditional Amsler Grid, the authors concluded that the LST could capture more cases of deformations in patients with ERM.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining a reliable map of deformations having a potential in opening new horizons in developing technologies that would potentially increase the quality of life of patients with macular diseases, it is not surprising that there have been an increasing number of reports in computer‐based metamorphopsia measurement methodologies in the literature in the past few years. One such method called the line sag test (LST) is a computerized psychophysical test in which the observer is presented briefly with a curved line and asked to report whether the line appears to bulge inwards or outwards 44 . Using a staircase procedure, an algorithm neutralizes the amount of perceived sag by presenting a curve at the opposite direction to the response of the patient in the next trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations